2020
DOI: 10.1063/1.5122984
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric nanotomography based on electrostatic force microscopy: A numerical analysis

Abstract: Electrostatic force microscopy (EFM) can image nanoscale objects buried below the surface. Here, we theoretically show that this capability can be used to obtain nanotomographic information, i.e., the physical dimensions and dielectric properties, of buried nano-objects. These results constitute a first step toward implementing a nondestructive dielectric nanotomography technique based on EFM with applications in materials sciences and life sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…This would require assigning different dielectric constants to each voxel of the local geometric model and to use advanced tomographic reconstruction algorithms, not available yet, despite the progress made recently. [48] The dielectric and composition mapping could be in principle extended to fixed cells in water environment and to living cells. Scanning dielectric microscopy has been already demonstrated in the water environment, [49,50,51] and it has been applied to probe the dielectric properties of systems like supported lipid bilayers, [52,53] self-assembled monolayers (SAMs), [54] and electrolyte gated field effect transistors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would require assigning different dielectric constants to each voxel of the local geometric model and to use advanced tomographic reconstruction algorithms, not available yet, despite the progress made recently. [48] The dielectric and composition mapping could be in principle extended to fixed cells in water environment and to living cells. Scanning dielectric microscopy has been already demonstrated in the water environment, [49,50,51] and it has been applied to probe the dielectric properties of systems like supported lipid bilayers, [52,53] self-assembled monolayers (SAMs), [54] and electrolyte gated field effect transistors.…”
Section: Discussionmentioning
confidence: 99%
“…This would require assigning different dielectric constants to each voxel of the local geometric model and to use advanced tomographic reconstruction algorithms, not available yet, despite the progress made recently. [ 48 ]…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the charge distribution in finite size systems (Yalcin et al ., 2012; Roy‐Gobeil et al ., 2015; Miyahara et al ., 2017), even in the presence of spatial, compositional and energy disorder (El Khoury, 2017), can be visualized by these techniques. Local electrostatic techniques provide information on the 2D spatial distribution of charge carriers in semiconductors (Chin et al ., 2008; Musumeci et al ., 2017), nanostructures (Krauss & Brus, 1999; Cherniavskaya et al ., 2003; Marchi et al ., 2008; Borgani et al ., 2016) and devices (Pingree et al ., 2009) and, more recently, in volume (3D) (Collins et al ., 2015; Fabregas & Gomila, 2020) and in time (Araki et al ., 2019; Borgani & Haviland, 2019; Mascaro et al ., 2019). These techniques were proven useful in studying the localization of trapped charges in thin films (Silveira & Marohn, 2004; Chen et al ., 2005a; Chen et al ., 2005b; Muller & Marohn, 2005), quantum dots (Tevaarwerk et al ., 2005) and nanotubes (Chin et al ., 2008); to measure the resistance at metal–semiconductor interfaces and grain boundaries in operating devices (Annibale et al ., 2007); to relate electrical properties, such as dielectric permittivity (Gramse et al ., 2009; El Khoury et al ., 2016; Fumagalli et al ., 2018), conductivity (Castellano‐Hernández & Sacha, 2015; Aurino et al ., 2016), piezoelectricity (Moon et al ., 2017) and percolation pathways (Barnes & Buratto, 2018), directly to the organization of the material at the mesoscopic length scales.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic force microscopy (EFM) is one of the subsurface SPM techniques that has experienced more progress toward its implementation as a nanotomographic technique for polymeric nanocomposite materials (Jespersen & Nygard, 2007; Castañeda-Uribe et al, 2015; Cadena et al, 2018; Fumagalli et al, 2018; Fabregas & Gomila, 2020). Subsurface EFM imaging is based on the long-range nature of the electric forces, which can sense the presence and position of nanoscale objects buried within a polymeric material.…”
Section: Introductionmentioning
confidence: 99%
“…The subsurface and nanotomographic capabilities of EFM applied to nanowire nanocomposites have not been specifically analyzed. Some theoretical studies have been reported for the case of nanoparticles, carbon nanotubes, and thin-film nanocomposites (Jespersen & Nygard, 2007; Riedel et al, 2011; Arinero et al, 2012; Castañeda-Uribe et al, 2015; Fabregas & Gomila, 2020), but they have not addressed some key aspects relevant for nanowires nanocomposites, namely the achievable spatial resolution or the possibility to detect the capacitive coupling between nearby nanowires. Here, we develop a numerical approach to specifically investigate these aspects and demonstrate that quantitative EFM, which we refer to as scanning dielectric microscopy (SDM), can be a valuable nanoscopic technique for the nondestructive characterization of nanowire nanocomposites.…”
Section: Introductionmentioning
confidence: 99%